1991
DOI: 10.1002/ajp.1350230402
|View full text |Cite
|
Sign up to set email alerts
|

Primate origins and the evolution of angiosperms

Abstract: Traditionally, the morphological traits of primates were assumed to be adaptations to an arboreal way of life. However, Cartmill [1972] pointed out that a number of morphological traits characteristic of primates are not found in many other arboreal mammals. He contends that orbital convergence and grasping extremities indicate that the initial divergence of primates involved visual predation on insects in the lower canopy and undergrowth of the tropical forest. However, recent research on nocturnal primates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
215
0
5

Year Published

1997
1997
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 323 publications
(230 citation statements)
references
References 46 publications
10
215
0
5
Order By: Relevance
“…These fibrous foods are low in readily digestible energy, higher in hemicellulose, cellulose and lignin than ripe fruit (Remis, 1997a,b,c Remis et al, 2001Rogers et al, 2004Rogers et al, ,1990Rothman et al, 2014), although in times of fruit scarcity fruits eaten are high in fiber and similar to vegetation (Remis et al, 2001). Thus, it is likely that bio-geographical and ecological factors across evolutionary timescales triggered both diversification of Gorilla spp., and the acquisition of distinct gut bacterial communities in mountain and lowland gorillas (Ley et al, 2008;Collins and Dubach, 2000;Gomez and Verdu, 2012;Sussman, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…These fibrous foods are low in readily digestible energy, higher in hemicellulose, cellulose and lignin than ripe fruit (Remis, 1997a,b,c Remis et al, 2001Rogers et al, 2004Rogers et al, ,1990Rothman et al, 2014), although in times of fruit scarcity fruits eaten are high in fiber and similar to vegetation (Remis et al, 2001). Thus, it is likely that bio-geographical and ecological factors across evolutionary timescales triggered both diversification of Gorilla spp., and the acquisition of distinct gut bacterial communities in mountain and lowland gorillas (Ley et al, 2008;Collins and Dubach, 2000;Gomez and Verdu, 2012;Sussman, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Textbooks of physical anthropology will tell you that there are three or four theories of primate origins: the old arboreal theory, which describes the euprimate traits (or trends) as the inevitable outcome of life in the trees; the similar ''grasp-leaping'' theory of F. S. Szalay, who sees the euprimate traits as having originated as adaptations to acrobatic leaping in trees; 39,40 my ''visual-predation'' theory; [35][36][37][38] and R. W. Sussman's thesis that the euprimate traits originated in connection with the exploitation of fruit and nectar. 41,42 But this narrative of conflicting theories falls apart on closer examination. Although one can imagine observations that would count decisively against some of these theories, 43 none of them is couched in terms of any defining metrics that would exclude the others.…”
Section: Simpson and Mesozoic Mammalsmentioning
confidence: 99%
“…Based on relative size of the optic foramen of Simonsius grangeri it appears that Oligocene anthropoids had already developed keen eyesight (Kirk and Kay 2004). Sussman (1991) argues that early primates needed acute powers of visual discrimination and precise coordination to manipulate small seeds and fruits. Trichromatic color vision may help primates distinguish fruit against a background of green leaves (Barton 2000) or may signal the nutritional value of fruit (Riba-Hernández et al 2005), although other possible hypothesized reasons for trichromacy have been suggested (e.g., Dominy 2004).…”
Section: An Evolutionary Scenariomentioning
confidence: 99%